Non-Synergistic UV-A Photocatalytic Degradation of Estrogens by Nano-TiO2 Supported on Activated Carbon - Rosa,Suzamar M. C. (2017)
Many studies have reported significant improvements in the photocatalytic degradation capacity of TiO2 immobilized in carbonaceous materials, mainly due to a well-characterized synergistic effect. The photocatalytic degradation of the estrogens 17β-estradiol and 17α-ethynylestradiol was evaluated using 1 mg L-1 aqueous solutions, employing a nanocomposite containing TiO2 and activated carbon (TiO2-AC) prepared by sol-gel technique. The synthesized materials were characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD), Raman spectroscopy and scanning electron microscopy (SEM). These techniques allowed to estimate the carbon proportion (11.4 wt.%), the phase composition (anatase: 80.2%, brookite: 14.0%, and rutile: 5.8%) and the superficial morphology. Using UV-A radiation provided by a high pressure mercury vapor lamp (125 W) and the synthesized photocatalysts, it was observed the almost complete removal of both estrogens in times shorter than 10 minutes. Considering the similarity between the degradation percentage of nanocomposites (TiO2 and TiO2-AC), no synergistic effects between AC and TiO2 could be assumed.